Jewish messiahs in a Christian empire : a history of the Book of Zerubbabel - Himmelfarb, Martha, 1952- (Harvard University Press, 2017)
Sefer Zerubbabel, the Book of Zerubbabel, is a Hebrew apocalyptic work composed during the wars between the Byzantine and Persian empires in the early decades of the seventh century of this era, shortly before the Muslim conquest of the Middle East. Himmelfarb places Sefer Zerubbael's narrative in the context of Christian tradition and contemporary Byzantine culture on the one hand and earlier Jewish eschatological traditions on the other. The impact of the Christian messianic narrative can be seen in Sefer Zerubbabel's depiction of the messiah son of David in terms of Isaiah's suffering servant and in the death and resurrection of the messiah son of Joseph, while contemporary Byzantine ideas about the Virgin as the patron and protector of Constantinople help to make sense of Sefer Zerubbabel's otherwise startling depiction of the mother of the messiah as a warrior defending Jerusalem. Sefer Zerubbabel also shows many points of contact with traditions about the messiah in rabbinic literature, but, the author argues, it is not dependent on the rabbinic formulation of those traditions. Rather, both the rabbis and Sefer Zerubbabel drew on popular traditions, which they reshaped for their own purposes. The rabbis tend to play down messianic hopes while Sefer Zerubbabel embraces them more enthusiastically. Thus reading Sefer Zerubbabel and rabbinic literature side by side allows us to recover some elements of the popular Jewish messianism of the early centuries of the Christian era. The book concludes by considering Sefer Zerubbabel's impact on a corpus of Jewish eschatological texts from the centuries after the rise of Islam.--